Ethnomedicinal survey of indigenous medicinal plants in Jos Metropolis, Nigeria - Babajide C. Falemara; Victoria I. Joshua; Temitope I. Ogunkanmi; Wilfred O. Mbeng (AOSIS, 2021)
Background: Indigenous knowledge is progressively fading out because of a lack of proper record-keeping, as the knowledge is transmitted verbally. There is, therefore, a dire need for preserving this valuable knowledge by ensuring proper documentation and sharing of traditional knowledge. Aim: This research study sought to explore the indigenous knowledge used by herbal medicine practitioners for treating various human ailments in Jos Metropolis of Plateau State, Nigeria. Setting: The study was conducted using a structured questionnaire administered to 100 registered traditional healers in Jos North LGA of Plateau State. Methods: Selected medicinal plants were collected, pressed and transported to the Forestry Research Institute of Nigeria (FRIN), Ibadan for identification, authentication and deposition of voucher specimens for voucher number at FRIN herbarium, Ibadan. Descriptive statistics were used to analyse the ethnomedicinal data. Results: Thirty-nine plant species, distributed in 33 families and 39 genera, were cited by the respondents. The Fabaceae was the most represented family, followed by the Euphorbiaceae and Myrtaceae. Leaves were the most used plant part (29%), whilstthe most cited plant habit forms include trees (48%) and herbs (31%). The herbal remedies were mostly administered orally (53%) and topically (26%), whilst the most common method of preparation was decoction (42%). The highest consensus factor (1.00) was detected for chickenpox or measles or leprosy, haemorrhoids and sickle cell ailments. Conclusion: There is an existence of a wide gap in traditional healing knowledge between the elderly and the younger generations in the study area. The high fidelity level observed in this study implied a general acceptance and preferred usage of such herbal plants for the treatment of particular ailments.